Investigation of the Dissipation Process in Electrolytic Capacitors. (1980) - Cathey, Leconte; Joyner, Keith A.
Abstract : An experimental study of electrolytic capacitors was conducted, with emphasis on their thermal properties. The capacitors were subjected to charge–discharge cycles with various values of peak voltage. The observed power dissipated did not agree with that which would be expected if constant capacitance and constant effective series resistance (ESR) are assumed for the capacitors. In order to explain the discrepancy, the capacitance and ESR variations were measured with respect to voltage, temperature, and frequency. A predicted power dissipation was calculated for each capacitor; these dissipations compared favorably with those that were experimentally observed. In addition, voltage versus time profiles were measured for each unit and these were analyzed to determine the charge transport characteristics of the capacitors. The populations and mobilities of each type of charge carrier turned out to be quite similar from one capacitor sample to the next.